Guide to Teaching Computer Science An Activity-Based Approach - Hazzan, Orit; Lapidot, Tami; Ragonis, Noa (Springer London : Imprint: Springer, 2014)
Demonstrating that computer science learning and teaching processes can be fun, thought-provoking and stimulating, this unique textbook presents both a conceptual framework and detailed implementation guidelines for computer science (CS) teaching. This highly-anticipated new edition has been updated with the latest teaching approaches and trends, and includes 110 learning activities (of which 15 are new). The content is clearly written and structured to be applicable to all levels of CS education and for any teaching organization, without limiting its focus to instruction of any specific institution, curriculum, programming language or paradigm. Topics and features: Provides 110 detailed learning activities to be facilitated in different class settings Reviews curriculum and cross-curriculum topics in CS Explores the benefits of CS education research Describes strategies for cultivating problem-solving skills, for assessing learning processes, and for dealing with pupils' misunderstandings Proposes active-learning-based classroom teaching methods, including lab-based teaching Discusses various types of questions that a CS instructor or trainer can use for a range of teaching situations in class, homework and tests Investigates thoroughly issues of lesson planning and course design Examines the first field teaching experiences gained by CS teachers across different training f rameworks This preeminent textbook for CS teacher training programs draws on the authors' experience gained from three decades of teaching and training prospective and in-service CS teachers, as well as research in CS education. Concise, thorough and easy-to-follow, the book is also eminently suitable for use as a teaching guide for CS instructors at all levels.